2000
DOI: 10.4269/ajtmh.2000.62.711
|View full text |Cite
|
Sign up to set email alerts
|

Markers of enteric inflammation in enteroaggregative Escherichia coli diarrhea in travelers.

Abstract: Abstract. As part of a traveler's diarrhea study carried out in Guadalajara, Mexico, and Goa, India, we conducted a case control study to evaluate fecal markers of enteric inflammation in three groups. Forty-five cases of enteroaggregative Escherichia coli (EAEC) diarrhea were compared to 56 controls with enterotoxigenic E. coli (ETEC) diarrhea, and 126 controls with diarrhea without identifiable pathogens. For EAEC cases we found fecal leukocytes, occult blood, and lactoferrin in 13 (28.9%), 14 (31.1%), and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 20 publications
(18 reference statements)
2
36
0
1
Order By: Relevance
“…Some studies have demonstrated an association of EAEC infection with inflammatory cytokines 53,54 and several others have associated EAEC with elevated lactoferrin levels. 15,55 In children with diarrhea, we found a significant statistical association of elevated fecal lactoferrin with the aap gene, and with the detection of any one or two of the EAEC genes tested ( P < 0.05). Between diarrhea and non-diarrhea stool specimens, EAEC's chromosomal gene aaiC was associated with the highest fold-rise in fecal lactoferrin level (2.7) followed by the aap gene (2.5).…”
mentioning
confidence: 81%
“…Some studies have demonstrated an association of EAEC infection with inflammatory cytokines 53,54 and several others have associated EAEC with elevated lactoferrin levels. 15,55 In children with diarrhea, we found a significant statistical association of elevated fecal lactoferrin with the aap gene, and with the detection of any one or two of the EAEC genes tested ( P < 0.05). Between diarrhea and non-diarrhea stool specimens, EAEC's chromosomal gene aaiC was associated with the highest fold-rise in fecal lactoferrin level (2.7) followed by the aap gene (2.5).…”
mentioning
confidence: 81%
“…Having received the first Early Warning Response System (EWRS) alert issued by the Robert Koch Institute (RKI) in Germany on 23 May about an increase in the number of patients presenting with haemolytic uraemic syndrome (HUS) and bloody diarrhoea caused by Shiga toxin-producing Escherichia coli (STEC) with more than 30 possible cases reported since the second week of May, the World Health Organization Collaborating Centre (WHO CC) for Reference and Research on Escherichia and Klebsiella at Statens Serum Institut (SSI) in Denmark issued an alert to the Danish E. coli network of regional hospitals on the same day. On 24 May, Hvidovre University hospital reported a German patient who had been diagnosed with Shiga toxin/verotoxin-producing E. coli (STEC/VTEC) and referred the strain to SSI.…”
Section: Sequence Of Eventsmentioning
confidence: 99%
“…EAggEC infections are usually associated with watery diarrhoea, which is often persistent [20]. Illness results from a complex interaction between pathogen and host, which implicates the initial adherence of the bacteria to the epithelium of terminal ileum and colon, by virtue of the aggregative adherence fimbriae (characteristic aggregative pattern), followed by a damage/secretion stage manifested by cytokine release, mucosal toxicity, intestinal secretion and induction of mucosal inflammation [22][23][24][25][26]. EAggEC is best known for its role in persistent diarrhoea (>14 days) in infants and children in developing countries.…”
Section: General Characteristics Of Eaggecmentioning
confidence: 99%
“…78 Lactoferrin, an iron-binding antimicrobial glycoprotein, 79 has been a target in other studies that demonstrate significantly increased levels of this protein alongside fecal leucocytes in EAEC infected patients. 80 Not surprisingly, CCL20, a dendritic cell recruiter, is also known to be upregulated after persistent EAEC stimulus. 73 Recently, our group published in vivo data reporting for the first time the importance of T helper (Th)17 cells in host responses to EAEC and EAEC clearance.…”
mentioning
confidence: 99%